MOTIVATION AND EMPATHY AS CORRELATES OF HELPING BEHAVIOR DURING FLOODS IN SERBIA IN 2014 - Trbojević, Jovana; Otašević, Biljana; Mitrović, Dušanka (Primenjena psihologija, 2015)
Helping behavior is a type of prosocial behaviors. Researchers are mainly interested in motivation behind helping. Hence, this paper examines helping behaviors during floods in Serbia, with motivation and empathy as correlates of the level of helping behaviors. The sample consisted of 204 individuals who helped during the flood (61.3% females), average age of 29.7 years. In June and August of 2014th, the participants completed questionnaires about the ways and the level of helping behaviors, a modified Volunteer Functions Inventory and the Assessment of Readiness for Empathy. Guided by the Functional Theory of Motivation, which distinguishes six motives for helping, we conducted a univariate analysis of covariance with all of the six motives and four subtypes of empathy as continues predictors and gender as a categorical predictor of the level of helping behaviors. The results show that this predictive model explains 30% of helping behaviors. Significant predictors were Understanding motive, Social motive, and Empathy with negative emotional states, while gender did not have a significant contribution. Motivation to help people in order to get to know the world and one’s abilities, to better understand the people and to enhance one’s social interaction, indicates the existence of both egoistic and altruistic motivation for helping during floods. During this crisis a relevant role in helping had an empathic paradox. Our results indicate simultaneous existence of a large number of motives as well as the role of empathy in helping behaviors. Practical implications of the results, as related to a better selection of people willing to help in time of crisis, were discussed.